Commercial laying hen diets formulated according to different recommendations of total and digestible amino acids - Casartelli, em [UNESP] (2005)
An experiment was conducted to evaluate different commercial laying hen diets formulated based on recommendations for total and digestible amino acids. One hundred and twenty Lohmann LSL commercial laying hens aged 25 weeks were distributed in a completely randomized experimental design involving five replications of six birds in four treatments. Diet formulation on a total amino acid basis followed the recommendations of NRC (1994) and Rostagno et al. (2000), whereas formulation on digestible amino acids basis was according to Rostagno et al. (2000) and Degussa (1997) recommendations. The experimental period was divided into five periods of fourteen days. Performance parameters (egg production, feed intake, feed conversion, egg mass) were evaluated for each period, and on the last two days of each period, three eggs per replication were collected to evaluate egg quality parameters (Haugh unit, egg specific gravity, egg weight, eggshell thickness and percentage). Means were compared by orthogonal contrasts. Results on feed intake, egg production, egg mass, feed conversion and egg specific gravity showed that total amino acid recommendations promoted better bird responses than digestible amino acid recommendations.